Hepatoprotective Role of Carvedilol against Ischemic Hepatitis Associated with Acute Heart Failure via Targeting miRNA-17 and Mitochondrial Dynamics-Related Proteins: An In Vivo and In Silico Study - Doaa I. Mohamed; Samar F. Ezzat; Wael M. Elayat; Omnyah A. El-Kharashi; Hanaa F. Abd El-Kareem; Hebatallah H. Abo Nahas; Basel A. Abdel-Wahab; Samar Zuhair Alshawwa; Asmaa Saleh; Yosra A. Helmy; Eman Khairy; Essa M. Saied (MDPI AG, 2022)
Acute heart failure (AHF) is one of the most common diseases in old age that can lead to mortality. Systemic hypoperfusion is associated with hepatic ischemia-reperfusion injury, which may be irreversible. Ischemic hepatitis due to AHF has been linked to the pathogenesis of liver damage. In the present study, we extensively investigated the role of mitochondrial dynamics-related proteins and their epigenetic regulation in ischemic liver injury following AHF and explored the possible hepatoprotective role of carvedilol. The biochemical analysis revealed that the ischemic liver injury following AHF significantly elevated the activity of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) enzymes, the level of total and direct bilirubin, and the expression of hepatic mitogen-activated protein kinase (MAPK), dynamin-1-like protein (DNM1L), and hepatic miRNA-17. At the same time, it significantly reduced the serum albumin level, the activity of hepatic superoxide dismutase (SOD), and the expression of mitochondrial peroxisome proliferator-activated receptor-1α (PGC-1α), and mitofusin 2 (Mtf2). The histological examination of the liver tissue revealed degenerated hepatocytes. Interestingly, administration of carvedilol either prior to or after isoprenaline-induced AHF significantly improved the liver function and reversed the deterioration effect of AHF-induced ischemic hepatitis, as demonstrated by biochemical, immunohistochemical, and histological analysis. Our results indicated that the hepatoprotective effect of carvedilol in ameliorating hepatic ischemic damage could be attributed to its ability to target the mitochondrial dynamics-related proteins (Mtf2, DNM1L and PGC-1α), but also their epigenetic regulator miRNA-17. To further explore the mode of action of carvedilol, we have investigated, in silico, the ability of carvedilol to target dynamin-1-like protein and mitochondrial dynamics protein (MID51). Our results revealed that carvedilol has a high binding affinity (−14.83 kcal/mol) toward the binding pocket of DNM1L protein. In conclusion, our study highlights the hepatoprotective pharmacological application of carvedilol to attenuate ischemic hepatitis associated with AHF.